Adding to the story, did penetrating trauma really increase? changes in trauma patterns during the COVID-19 pandemic: A multi-institutional, multi-region investigation. Issue 6 (June 2022) - Mokhtari, Ava K; Maurer, Lydia R; Dezube, Michael; Langeveld, Kimberly; Wong, Yee M.; Hardman, Claire; Hafiz, Shabnam; Sharrah, Mark; Soe-Lin, Hahn; Chapple, Kristina M; Peralta, Rafael; Rattan, Rishi; et al.
Highlights: Blunt traumatic injury volumes decreased secondary to decreased MVCs during the initial four months of the COVID-19 pandemic. Penetrating injury increased during the first four months of the COVID-19 pandemic, along with a significant increase in GSW volume. Stay at home orders (SAHOs) were associated with the observed decrease in blunt injuries, specifically decreased MVCs. 4. Stay at home orders did not account for observed volume changes in non-MVC related blunt injuries or penetrating injuries. Abstract: Background: Results from single-region studies suggest that stay at home orders (SAHOs) had unforeseen consequences on the volume and patterns of traumatic injury during the initial months of the Coronavirus disease 2019 (COVID-19). The aim of this study was to describe, using a multi-regional approach, the effects of COVID-19 SAHOs on trauma volume and patterns of traumatic injury in the US. Methods: A retrospective cohort study was performed at four verified Level I trauma centers spanning three geographical regions across the United States (US). The study period spanned from April 1, 2020 – July 31, 2020 including a month-matched 2019 cohort. Patients were categorized into pre-COVID-19 (PCOV19) and first COVID-19 surge (FCOV19S) cohorts. Patient demographic, injury, and outcome data were collected via Trauma Registry queries. Univariate and multivariate analyses were performed. Results: A total 5, 616 patients presented to participating study centers during the PCOV19 (2, 916) and FCOV19S (2, 700) study periods.  Blunt injury volume decreased ( p  = 0.006) due to a significant reduction in the number of motor vehicle collisions (MVCs) ( p  = 0.003). Penetrating trauma experienced a significant increase, 8% (246/2916) in 2019 to 11% (285/2, 700) in 2020 ( p  = 0.007), which was associated with study site ( p  = 0.002), not SAHOs. Finally, study site was significantly associated with changes in nearly all injury mechanisms, whereas SAHOs accounted for observed decreases in calculated weekly averages of blunt injuries ( p < 0.02) and MVCs ( p = 0.003). Conclusion: Results of this study suggest that COVID-19 and initial SAHOs had variable consequences on patterns of traumatic injury, and that region-specific shifts in traumatic injury ensued during initial SAHOs. These results suggest that other factors, potentially socioeconomic or cultural, confound trauma volumes and types arising from SAHOs. Future analyses must consider how regional changes may be obscured with pooled cohorts, and focus on characterizing community-level changes to aid municipal preparation for future similar events.